Research on Lightning Overvoltage of Oil-Gas Pipeline Caused by Lightning Strikes on Adjacent Electrical Transmission Line - Hu, Shangmao; Hu, Yuanchao; Wang, Jing; An, Yunzhu; Liu, Gang; Liu, Zhixiang; Cheng, Yan (Frontiers in Energy Research, 2022)
As natural lightning strikes on a transmission tower, lightning current will flow along grounding lines into the adjacent tower grounding grid. As lightning current is dispersed from the tower grounding grid into the soil, a lightning overvoltage may be produced on adjacent pipelines. In this paper, the lightning current shunt characteristics in multi-tower scenarios are calculated by simulation method under different soil resistivity conditions. Then, based on the lightning current shunt characteristics, the current dispersion process among multi-tower grounding grids and the pipeline is analyzed with different soil resistivities, gap distances, and lightning current amplitudes. Finally, the protective effect of “drain wire” and “forced commutation” on pipeline overvoltage are compared. Simulation results showed that with increasing soil resistivity, tower grounding resistance was increased and tower shunt coefficient decreased. Considering lightning current through the multi-tower grounding grids, pipeline overvoltage is much larger than that of a single tower. Pipeline overvoltage is increased with soil resistivity and lightning current amplitude, while it is decreased with “pipeline-line” distance. Both “drain wire” method and “forced commutation” method can effectively reduce pipeline potential.